Biogeographic implications of fossil fishes from the Awash River, Ethiopia. Issue 1 (2nd January 2017) - Stewart, Kathlyn M.; Murray, Alison M.
ABSTRACT: The late Miocene and Pliocene Middle Awash fish fauna is one of the earliest known Neogene fish faunas in eastern Africa and is the earliest known from the Horn of Africa. The fauna was recovered as part of the Middle Awash research project, which was designed to investigate the Mio-Plio-Pleistocene deposits along the shores of the Awash River, Ethiopia. Remains of eight fish taxa were recovered: Clarotes, Cichlidae, and Parachanna, which are native to the African continent where they have a long fossil record, and cf. Labeo, Barbus, Labeobarbus, Bagrus, and Clarias, whose origins were in Asia. These genera and families are all extant; however, certain fossil elements of cf. Labeo and Bagrus differ morphologically from modern species. When and how the Asian-derived taxa moved into Africa is enigmatic. The Middle Awash fossil deposits are located within the Horn of Africa, long suggested as a possible crossing point between Africa and the Arabian Peninsula in the late Miocene. Data presented in this paper suggest that in the late Miocene, the Horn of Africa region was accessible from the southern Arabian Peninsula via the Bab el-Mandeb Strait land bridge, which was (only) viable in the late Miocene. This land bridge has been implicated in the migration of other freshwater and terrestrial animals between Africa and Arabia. The subsequent movement of Barbus sp., Labeobarbus sp., Bagrus sp., and Clarias sp. into eastern Africa had a large impact on the diversity and abundance of later populations of African freshwater fish. Citation for this article: Stewart, K. M., and A. M. Murray. 2017. Biogeographic implications of fossil fishes from the Awash River, Ethiopia. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1269115.